La familia ayer, hoy y siempre : reflexiones desde distintas disciplinas - Domínguez Hidalgo, Carmen Aída; Corbalán, Cecilia (Ediciones Universidad Católica de Chile, 2013)
The family is, and has been, the privileged, unique and irreplaceable space in people's lives. And that, which sometimes seems obvious but at other times not so clear, is what this book shows us. At all times the family has been at the center of personal and social life. By the way, it has been in different ways, with different emphases, with transformations, but, with everything, always at the center. That has also been the objective of the seven versions of the conferences that have served as the basis for this publication, given by each of its authors on the occasion of the Seminar with which each year we inaugurate the new version of the Family and Society Diploma that we teach. Our intention has been to promote a reflection on the family from the different perspectives that an evolutionary view can give us.